SEQUENCE AND STRUCTURAL ANALYSIS OF PATHOGENESIS RELATED PROTEIN CLASS I CHITINASE FROM SEED COAT OF GLYCINE MAX [L.] MERR - MANVENDRA SINGH,; A. K. RAI, (The Bioscan, 2015)
Chitinase are enzymes that catalyze the hydrolysis of β-1,4-N-acetylglucosamine linkage present in chitin. Chitin is a major component of fungal cell walls, chitinases play a role in plant defense against pathogens. Proteomic studies carried on 32 kDa class I chitinase of soybean seed coat, the FASTA sequences for enzyme were taken from NCBI. The sequence with known PDB structure was taken for multiple sequence alignment. The sequences were compared with BLOSUM 62 matrix. The sequence similarity among these chitinases varied between 30 to 70 %, with maximum similarity exists between soybean seed coat chitinase and rice chitinase.Homology modeling at SWISS- MODEL gave 3 models with different scores. The model 1developed using jack bean chitinase has highest homology. Two conserved domain ChtBD1 [cd00035], Chitin binding domain, involved in recognition or binding of chitin subunits and Glycoside hitinase_glyco_hydro_19[cd00325], Glycoside hydrolase family 19 chitinase domain were detected in the sequence using Conserved domain detection tool at NCBI. Soybean seed coats are particularly rich in defense related proteins and peptides, although there are abundant proteins that have yet to be identified.In this study revealed complex structure and more refined mechanism of the chitinase catalysis.